2017
DOI: 10.1073/pnas.1706907114
|View full text |Cite
|
Sign up to set email alerts
|

First critical repressive H3K27me3 marks in embryonic stem cells identified using designed protein inhibitor

Abstract: The polycomb repressive complex 2 (PRC2) histone methyltransferase plays a central role in epigenetic regulation in development and in cancer, and hence to interrogate its role in a specific developmental transition, methods are needed for disrupting function of the complex with high temporal and spatial precision. The catalytic and substrate recognition functions of PRC2 are coupled by binding of the N-terminal helix of the Ezh2 methylase to an extended groove on the EED trimethyl lysine binding subunit. Disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 36 publications
(29 reference statements)
1
64
1
Order By: Relevance
“…The JARID2 2iL-I-F hESC mutants showed reduced H3K27me3 epigenetic repressive marks and reduced stem cell marker signature, showing that JARID2 is required to maintain the stem cell 2iL-I-F pluripotency state. PRC2 is not required in earliest na€ ıve state in mouse or human but shows requirement in the 2iL-I-F state [20]. We show that while other PRC2 components are expressed in both stages, JARID2 is dramatically downregulated in the earliest, 5iLA but not in the 2iL-I-F state.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The JARID2 2iL-I-F hESC mutants showed reduced H3K27me3 epigenetic repressive marks and reduced stem cell marker signature, showing that JARID2 is required to maintain the stem cell 2iL-I-F pluripotency state. PRC2 is not required in earliest na€ ıve state in mouse or human but shows requirement in the 2iL-I-F state [20]. We show that while other PRC2 components are expressed in both stages, JARID2 is dramatically downregulated in the earliest, 5iLA but not in the 2iL-I-F state.…”
Section: Introductionmentioning
confidence: 68%
“…Since multiple pluripotent stages have been stabilized from early human development [10][11][12][13][14], it is critical to analyze if PRC2 components are required for stemness in these stages. Using a computationally designed new protein, EED binder, we recently showed that similar to mouse, the earliest na€ ıve 5iLA hESC state is PRC2-independent, however, PRC2 is required to maintain na€ ıve 2iL-I-F and primed hESC pluripotent states [20]. Therefore, PRC2 is not required in earliest na€ ıve state in either mouse or in human, but is required in later stages [20].…”
Section: Jarid2 Expression In Pluripotent Stagesmentioning
confidence: 99%
“…Interestingly, preventing the redistribution of epigenetic marks during the transition to a naïve state is sufficient to block changes in chromatin compaction at several exemplar regions, thereby directly linking epigenome remodelling with aspects of genome organisation (McLaughlin et al). The transcriptome and cell state of mouse and human naïve PSCs are largely unaffected by experimentally disrupting Polycomb levels (Galonska et al, 2015;Moody et al, 2017;Riising et al, 2014;Shan et al, 2017). In contrast, primed PSCs are sensitive to the removal of Polycomb proteins (Collinson et al, 2016;Moody et al, 2017;Shan et al, 2017;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome and cell state of mouse and human naïve PSCs are largely unaffected by experimentally disrupting Polycomb levels (Galonska et al, 2015;Moody et al, 2017;Riising et al, 2014;Shan et al, 2017). In contrast, primed PSCs are sensitive to the removal of Polycomb proteins (Collinson et al, 2016;Moody et al, 2017;Shan et al, 2017;Wang et al, 2018). These observations collectively imply that the stable transition from a naïve to a primed state of pluripotency requires the reconfiguration of DNA interactions to provide a coordinated set of 'poised' regulatory signals to control promoter priming.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some naive-specific genes (such as DPPA3 and TBX3) are activated relatively early, others (such as DPPA5, KLF17 and ZFP57) are fully induced only upon subsequent passaging (Collier et al, 2017). Naive resetting of hPSCs also involves profound metabolic changes, including increased oxidative phosphorylation (Takashima et al, 2014;Sperber et al, 2015) and glycolytic metabolism (Gu et al, 2016), and confers tolerance to the removal or inhibition of PRC2 enzymes (Moody et al, 2017;Shan et al, 2017).…”
Section: Interconversions Between Distinct Human Pluripotent Statesmentioning
confidence: 99%